Pengaruh Model Pembelajaran Demonstrasi Terhadap Kemampuan Psikomotorik Gerak Dasar Lari dan Lompat Siswa di Sekolah Dasar - Emon Ramadhan Putra; Amir Luthfi; Nurmalina Nurmalina (Journal of Innovation in Teaching and Instructional Media, 2026)
This study aims to examine the effect of the demonstration learning model on the psychomotor skills of basic running and jumping movements among elementary school students. The background of this research is the low level of students’ psychomotor abilities in physical education, particularly in performing fundamental movements such as running and jumping, which is often caused by the use of less appropriate teaching methods. The study used a quantitative approach with a quasi-experimental design, specifically the One Group Pretest-Posttest Design. The research subjects were 20 fifth-grade students at SDN 007 Pangkalan Kerinci. Data were collected through psychomotor skill tests and learning interest questionnaires. The results showed that the demonstration learning model had a significant impact on improving students’ psychomotor skills in basic running and jumping movements. By observing correct movements directly, students were able to better understand the material, increase their motivation, and actively engage in physical education activities. Therefore, the demonstration method is recommended as an effective strategy to enhance students’ motor skill achievement at the elementary school level.